TRANSFORMATION OF ART EDUCATION IN ELEMENTARY SCHOOLS IN THE DIGITAL ERA: A LITERATURE REVIEW ON APPROACHES, MEDIA, AND INNOVATIVE TECHNOLOGIES - Maharani, Okvi; Rokhman, Fathur; Wagiran; Hartono (Journal of Social Science, 2024)
Objective: This research aims to analyze the transformation of art education in elementary schools in the digital era by exploring literature on approaches, media, and innovative technologies applied in art education. It seeks to identify how digital advancements can enhance traditional learning models to meet the needs of the digital generation. Method: A literature review method was employed, collecting and analyzing recent studies and publications on innovative practices in elementary school art education. The review focused on project-based learning (PjBL), interactive media such as educational videos, Augmented Reality (AR), and multimedia applications. Results: The study found that innovative media and technologies significantly improve the effectiveness of art education by fostering contextual and interactive learning experiences. These innovations increase student engagement, motivation, and understanding of art. However, challenges such as limited infrastructure and insufficient digital skills among teachers remain significant barriers to effective implementation. Novelty: This research provides comprehensive insights into the role of digital technologies in transforming art education in elementary schools. It highlights the necessity of culturally relevant content, teacher training, and tailored implementation strategies to address infrastructural and pedagogical challenges, offering a roadmap for optimizing art education in the digital era.